Optimizing U.S. Air Force and Department of Defense review of Air Force acquisition programs (National Academies Press, 2009)
The Department of Defense (DOD) spends over $300 billion each year to develop, produce, field and sustain weapons systems (the U.S. Air Force over $100 billion per year). DOD and Air Force acquisitions programs often experience large cost overruns and schedule delays leading to a loss in confidence in the defense acquisition system and the people who work in it. Part of the DOD and Air Force response to these problems has been to increase the number of program and technical reviews that acquisition programs must undergo. This book looks specifically at the reviews that U.S. Air Force acquisition programs are required to undergo and poses a key question: Can changes in the number, content, or sequence of reviews help Air Force program managers more successfully execute their programs? This book concludes that, unless they do it better than they are now, Air Force and DOD attempts to address poor acquisition program performance with additional reviews will fail. This book makes five recommendations that together form a gold standard for conduct of reviews and if implemented and rigorously managed by Air Force and DOD acquisition executives can increase review effectiveness and efficiency. The bottom line is to help program managers successfully execute their programs.